The Effect of Integrating Brain Vitalization Exercises to Low Impact Aerobic Exercises on Cognitive Improvement of the Elderly - Faiza Khansa Khairunnisa; Roikhatul Jannah; Dwi Agustina; Erna Sariana; Restu Arya Pambudi (poltekkes kemenkes mataram, 2025)
Cognitive function in the elderly refers to conscious mental activities such as thinking, remembering, learning, and using language. Cognitive impairments in the elderly can affect various aspects of life, including physical ability, independence in daily activities, and social relationships. Purpose of this study is to determine the effect of integrating brain vitalization exercises to low impact aerobic exercise on cognitive improvement in elderly individuals aged 65-75 years. This study employs a quasi-experimental design with a two-group pretest-posttest approach. A total of 26 samples were selected using purposive sampling and divided into two groups: 13 elderly participants in the Low Impact Aerobic Exercise group and 13 in the group that combined brain vitalization exercises with low impact aerobics. The independent variable was the addition of brain vitalization exercises, and the dependent variable was cognitive function, measured using the GPCOG score instrument. Data analysis included the Shapiro-Wilk normality test and Paired Sample T-Test for hypothesis testing. Results showed that the average cognitive score before the intervention in the treatment group 1 was 5.58, and after the intervention, it was 7.77, with a p-value 0.000 (<0.05). The mean balance score before intervention in treatment group 2 was 5.54, and after the intervention, it was 7.08, with a p-value of 0.000 (<0.05) 0.000 (<0.05). The mean difference in treatment group 1 was 0.04, and in treatment group 2, it was 0.69, with a p-value of 0.111 (>0.05). Low-impact aerobic exercise significantly improves cognitive function in the elderly. However, the addition of brain vitalization exercises did not provide a statistically significant additional benefit. This type of exercise is still recommended as a regular activity to support cognitive health in older adults.